The death of trooper Alexander Aberline, F Squadron, NSW Imperial Bushmen at Lichtenburg 2 October 1900 - John Bottomley (Contree, 2005)
Much of the history of the Anglo-Boer War is dour and brutal, as is to be expected of a three year struggle which many believed was genocidal in purpose. This war saw so many nationalities fighting against each other, and was at the same time a civil war involving Afrikaner against Afrikaner, and South African Englishspeakers, as well as many black combatants, fighting and dying on both sides. Yet, there was an emotional dimension to the war, although this level has so often been lost in the ‘grand overview’. This paper relates the story of one Australian combatant and his journey towards death in a foreign land. Trooper Aberline’s sacrifice was to have an impact on the Boers and his legacy went far beyond his rusting cross in the Lichtenburg cemetery which lies close to that of Edith Mathews who was buried nearby.